PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014) - Kartika Damayanti; Dyah Fitriani (Universitas Ahmad Dahlan, 2016)
Timeliness of the submission of Go's financial statements public is important for disclosing accounting information used by market participants in the investment decision-making process. This study aims to find empirical evidence about the factors that are affect the timeliness of financial reporting of manufacturing sector companies the consumer goods industry which is listed on the Indonesia Stock Exchange. Factors tested in this study are return on assets, current ratio, and total assets. The population in this study is the Industrial Sector Manufacturing Company Consumer goods a total of 40 companies are then taken as many samples 28 companies use purposive sampling techniques. Analytical techniques used logistic regression with a confidence level of 5%. The results of the study shows that profitability has a significant effect on accuracy financial reporting time, whereas liquidity and company size are not significantly influence the timeliness of financial reporting.